A Model for Predictive Measurements of Advertising Effectiveness - Lavidge, Robert J.; Steiner, Gary A. (Journal of Marketing, 1961)
The development and selection of research designs too often reflects thinking which is technique-oriented. This article looks at advertising research from another viewpoint. It starts with the questions: What is advertising supposed to do? What are its functions? The authors then show the implications of these questions in relation to measurements of the effectiveness of proposed advertisements.